Evaluate. \[ \begin{array}{c}-(2)^{4}=\square \\ (-4)^{3}=\square\end{array} \]
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
![](/pmw/light_bulb.png?etag=525fd69ac661e11754e2fc9f1b18a4ee)
![](/pmw/spiral_notepad.png?etag=abe3906b7558c543a7b30ba53a3b5a5b)
Mind Expander
Let's evaluate each expression step by step. 1. For the first expression, \(- (2)^{4}\): - First, calculate \((2)^{4}\): \[ (2)^{4} = 2 \times 2 \times 2 \times 2 = 16 \] - Now, apply the negative sign: \[ - (2)^{4} = -16 \] So, \(- (2)^{4} = -16\). 2. For the second expression, \((-4)^{3}\): - To find \((-4)^{3}\), compute: \[ (-4)^{3} = (-4) \times (-4) \times (-4) \] - Calculate \((-4) \times (-4)\): \[ (-4) \times (-4) = 16 \] - Now, multiply that result by \(-4\): \[ 16 \times (-4) = -64 \] Thus, \((-4)^{3} = -64\). In summary: \[ \begin{array}{c} -(2)^{4} = -16 \\ (-4)^{3} = -64 \end{array} \]
![](/pmw/img-try-permium.webp)